In it Together: Relationship Transitions and Couple Concordance in Health and Well-Being - Pauly, Theresa; Weber, Elisa; Hoppmann, Christiane A; Gerstorf, Denis; Scholz, Urte (My University, 2023)
Events that change the family system have the potential to impact couple dynamics such as concordance, that is, partner similarity in health and well-being. This project analyzes longitudinal data (≥ two decades) from both partners of up to 3,501 German and 1,842 Australian couples to investigate how couple concordance in life satisfaction, self-rated health, mental health, and physical health might change with transitioning to parenthood and an empty nest. Results revealed couple concordance in intercepts (averaged r = .52), linear trajectories (averaged r = .55), and wave-specific fluctuations around trajectories (averaged r = .21). Concordance in linear trajectories was stronger after transitions (averaged r = .81) than before transitions (averaged r = .43), whereas no systematic transition-related change in concordance of wave-specific fluctuations was found. Findings emphasize that shared transitions represent windows of change capable of sending couples onto mutual upward or downward trajectories in health and well-being.
Personality and Social Psychology Bulletin
Keywords: couples; empty nest; health; parenthood; well-being; Families and relationships; Health and wellbeing